Glossary of terms in official statistics : English-French, French-English - Nixon, James William; International Statistical Institute (Edinburgh ; London : Published for the International Statistical Institute by Oliver & Boyd, 1964)
The present list is a complete revision of the provisional list and it now contains about 1,500 main terms and in addition about 3,000 subsidiary terms, illustrating the application of these main terms.
Compiled on behalf of the International Statistical Institute and with the co-operation of its Permanent Office by J. W. Nixon.
Includes bibliographical references: p. 105-106.
ne 07/09/2021
Ref.
Keywords: Statistics; English language; French language